Analisis Kelayakan Pengembangan Usaha Snack Bocil dengan Metode Cost Benefit Analysis di Singosari Malang - Rahmat, Habib Abdullah; Indriani, Sri; Kertaningtyas, Mariza (Fakultas Teknik Universitas Tulang Bawang, 2025)
Dua Putra is a snack industry that produces Snack Bocil in the form of stick noodles with three flavors, namely seaweed, barbecue, and spicy. As the main product, Snack Bocil has received a positive response in the market with a distribution coverage that extends to Papua. However, in 2024, the company faces challenges in the form of drastically increasing consumer demand that exceeds the available production capacity. This condition requires the company to immediately increase production capacity through investment in equipment and expansion of production areas in order to meet consumer demand, maintain company growth, and maintain its reputation in the market. This study uses the Cost-Benefit Analysis (CBA) method with the help of demand forecasting using the Simple Moving Average method to determine the annual production target of 3,031 bals per month. The analysis is carried out using financial indicators such as NPV, PP, IRR, ROI, and PI to assess the feasibility of the investment. The results of the study indicate that business development is feasible with an NPV value of Rp 2,605,315, PP for 3 years and 7 months, IRR of 12.42%, ROI of 27.74%, and PI of 0.96, where in addition to the Payback Period, all indicate that the business development decision is not feasible. Thus, this business development step is expected to help the company meet market needs, increase production capacity, and make a significant contribution to sustainable business growth. Keywords: Business Feasibility Analysis, Cost Benefit Analysis (CBA), Forecasting.